Factors affecting health-promoting services provision of the sub-district health promoting hospital transferred to mahasarakham provincial administration - Sirimaporn Nassapat; Vorapoj Promasatayapot; Jatuporn Luangub (Intelektual Pustaka Media Utama, 2026)
Hospital services have been transferred to provincial government oversight, making it important to assess the impact of this policy on service quality and efficiency. This study examined factors influencing service delivery at sub-district health-promoting hospitals transferred to the Mahasarakham Provincial Administration in Mahasarakham Province, Thailand. The research was conducted from March 2022 to September 2023 using a mixed-methods approach, including descriptive content analysis for qualitative data. The examined factors were categorized into accessibility, processes, productivity, and outcomes. Data were collected from 500 health workers and 300 patients using questionnaires consisting of six sections with a Likert scale to evaluate perceptions of service quality. Paired t-tests were applied to compare service unit performance before and after the transfer, while one-way ANOVA was used to assess differences among service units. Binary logistic regression identified key factors influencing service quality. The findings revealed a significant relationship between healthcare workers’ attitudes and skills and overall service quality. Units with less than 50% transfer showed minimal improvement, indicating that the extent of transfer strongly influences service outcomes. Despite these differences, the main goal of health promotion remained consistent across units. Effective policy decisions, appropriate management, and stakeholder engagement are essential to improve health outcomes. These findings provide insights for policymakers and administrators to refine health service transfer policies and highlight the need for further research on long-term impacts on service quality and patient outcomes.